Fakta Anemia pada Remaja: Masalah Gizi yang Sering Diabaikan Banyak Orang - Cindy Renita; Eva Novianti; Salsabila Salsabila; Usman Usman (Media Literasi Indonesia, 2025)
Anemia is a condition in which the number and size of red blood cells or the level of hemoglobin fall below the established threshold. The purpose of this study is to identify the main factors causing anemia in adolescents from a nutritional and public health perspective. This study uses a literature review method, utilizing journals or articles from Google Scholar. The results show that there is a relationship between nutritional status and the incidence of anemia, especially in adolescent girls, as well as the influence of knowledge, education, and sleep quality. The conclusion is that the occurrence of anemia can affect the nutritional status of adolescents, leading to physical and mental growth disorders, increased risk of giving birth to low birth weight (LBW) infants, and other health issues